Potential mechanisms of natural metabolites and botanical drugs foumulae for the treatment of non-alcoholic fatty liver disease: targeting the gut microbiota to modulate the immune system - Zhang, Yutian; Liu, Lang; Song, Ruihao; Qu, Ziyi; Wang, Tianlin; Liang, Lei; Wang, Shunhua; Zhang, Shuzhi; Li, Huizhen; Wang, Hong (Frontiers in Pharmacology, 2025)
Non-alcoholic fatty liver disease (NAFLD) has become the most prevalent liver disorder worldwide and is also a significant risk factor for triggering non-alcoholic steatohepatitis (NASH), hepatic fibrosis, and liver cirrhosis. Disorders in the hepatic immune system constitute one of the key drivers of NAFLD progression; thus, targeting immune dysregulation may represent an effective strategy to delay or reverse NAFLD advancement. Meanwhile, gut microbiota (GM) and its metabolites directly influence liver immune responses throughthe “Gut-Liver Axis.” Dysbiosis of the GM triggers damage to the intestinal mucosal barrier. Subsequently, substantial bacterial metabolites derived from GM can induce overactivation of the hepatic immune response, thereby driving NAFLD progression. Thus, targeted intervention in the GM-immune response axis represents an effective therapeutic approach against NAFLD advancement. Numerous current studies indicate that botanical drugs and their metabolites can counteract NAFLD progression by intervening in GM and its metabolites to regulate hepatic immune imbalance. This article reviews the roles of immune cells, GM, and their metabolites in NAFLD development, while exploring the targets and/or pathways through which botanical drugs and their metabolites modulate GM and hepatic immune responses. This aims to provide a foundation for utilizing botanical drugs as natural adjuvants to address immune dysregulation during NAFLD treatment.